Congestive heart failure and hypertension associated with Wilms tumor - Sarah C. Stokes; Alyssa R. Bellini; Oleg Kovalenko; Lisa P. Abramson (Elsevier, 2021)
Wilms tumor is the most common primary renal tumor in children. Wilms tumor has infrequently been reported to present associated with dilated cardiomyopathy and congestive heart failure. In prior case reports of Wilms tumor presenting with congestive heart failure, surgical intervention has taken place after stabilization of heart failure. Here we present the first reported case of a child with Wilms tumor associated with congestive heart failure, requiring emergent operative intervention due to tumor rupture and hemorrhage.